The Risk of Pregnancy and Labour during the Covid19 Pandemic Relationship to Children's Health Insurance Related To Law No 35 of 2014 Concerning Child Protection and Law No 36 of 2009 about Health - Mukhlis, Muchammad Fauzan; Fauziah, Faridatul (Budapest International Research and Critics University, 2021)
Pregnancy and childbirth are happy moments for every mother-to-be in the world. However, pregnancy and childbirth during a pandemic have risks for transmission to both the mother and the fetus. Thus, giving attention to children is given since the child is conceived, during the delivery process and after delivery. During the COVID-19 pandemic, mothers can check their pregnancy 6 times during pregnancy. Preparing to give birth during the COVID-19 pandemic needs to be considered. The choice of place to give birth, be it at home, clinic, or hospital, taking into account the risks and benefits. After the baby is born it is important to continue to do consultations, including undergoing routine immunizations. Every mother should be more active in asking about safe ways to make appointments for consultations and immunizations in the midst of a pandemic. Given the bad impact, the government pays special attention to child protection by issuing Law Number 35 of 2014 concerning Child Protection in Article 1 it is stated that children are given special protection, namely a form of protection received by children in certain situations and conditions to get guarantees. a sense of security against threats that endanger themselves and their lives in their growth and development. Law Number 36 of 2009 concerning Health states that maternal health efforts must be aimed at maintaining maternal health so that they are able to give birth to a healthy and quality generation and reduce maternal mortality. Therefore, the role and alertness of the government and health workers as the front line in handling Covid-19 can provide peace to pregnant women through pregnancy and childbirth in the midst of a pandemic. Pregnant women need to pay more attention to complying with health protocols even though they have made an agreement to consult with health workers when preparing for pregnancy and childbirth during the COVID-19 pandemic